Evaluation of drip irrigation emitters arrangement and its effect on soil moisture, leaf nutrients, yield and quality of Nagpur mandarin (Citrus reticulata) - SHIRGURE, P S; SRIVASTAVA, A K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment on different arrangement of emitters in surface micro irrigation system in 14-16 years old Nagpur mandarin (Citrus reticulata Blanco) was conducted during 2010-2013 at the research farm of National Research Centre for Citrus, Nagpur. Four different treatments were used, viz. T1 - 4 lph six emitters/plant in hexagonal arrangement, T2 - 4 lph three emitters on double lateral arrangement at 1 spacing T3 - 4 lph eight emitters on single lateral in octagonal arrangement and T4 - 3 lph inline emitters at 0.75 m spacing on the lateral and double lateral arrangement 3 feet apart from trunk. Each treatment combination had different emitter placement and different irrigation interval with same water quantity. The average quantity of water applied different emitters arrangement of drip irrigation systems varied from 78.2 to 108.2 l/day/plant with 4 lph eight emitters on single lateral in octagonal arrangement during 2010-2013. The higher and uniform soil moisture distribution and plant canopy volume was observed in 4 lph eight emitters on single lateral in octagonal arrangement (84.96 m3) followed in 4 lph six emitters on single lateral in hexagonal arrangement (81.87 m3). The results indicated that the moisture distribution and yield was higher (28.78 tonnes/ha) under treatment with 4 lph eight emitters on single lateral in octagonal arrangement followed by treatment with 3 lph inline emitters at 0.75 m spacing on the lateral and double lateral arrangement 3 feet apart from trunk (27.26 tonnes/ha). The TSS to acidity ratio was the highest (13.9) with treatment 3 lph inline emitters at 0.75 m spacing on the lateral and double lateral arrangement 3 feet apart from trunk followed by with 4 lph eight emitters on single lateral in octagonal arrangement (12.4) of drip irrigation system. For higher yield and quality mandarin fruits the 4 lph (8 per plant) on single lateral is suggested.